Out-of-hospital Cardiac Arrest across the World: First Report from the International Liaison Committee on Resuscitation (ILCOR). - Kiguchi, Tekeyuki; Okubo, Masashi; Nishiyama, Chika; Maconochie, Ian; Ong, Marcus Eng Hock; Kern, Karl B; Wyckoff, Myra H; McNally, Bryan; Christensen, Erika; Tjelmeland, Ingvild; Herlitz, Johan; Perkins, Gavin D; et al. (2020)
BACKGROUND: Since development of the Utstein style recommendations for the uniform reporting of cardiac arrest, increasing numbers of national and regional out-of-hospital cardiac arrest (OHCA) registries have been established worldwide. The International Liaison Committee on Resuscitation (ILCOR) created the Research and Registries Working Group and aimed to systematically report data collected from these registries.